The British Mediterranean Fleet’s 1929 Visit to Türkiye in the Context of Turkish-British Relations - Resul Köse (Yakın Dönem Türkiye Araştırmaları)
Friendly relations could not be established between Türkiye and Britain until 1929. In order to improve bilateral relations, Türkiye invited the British Mediterranean Fleet for a courtesy visit. This study discusses the British Mediterranean Fleet’s 1929 visit to Türkiye, which has a very important place in the development of Turkish-British relations. The results of the study show that the British had been very satisfied with this visit. However, some states, especially Greece and Soviet Russia, were bothered by it and the visit also occupied the agenda of some states through the press. Türkiye explained the purpose of this visit through foreign representatives. In conclusion, this visit can be stated to have been a milestone in developing relations between Türkiye and Britain. In addition, the importance other states attached to the visit is a good example in terms of showing Türkiye’s effectiveness regarding foreign policy under the leadership of Gazi Mustafa Kemal in those years. This study has been conducted by making use of archival documents, periodicals, and copyrighted works as a qualitative study that was prepared using the document analysis method.